(untitled) (NAU Journal of Technology and Vocational Education, 2024)
The purpose of this study is to assess the performance of university business education graduates working in registered business establishments in Anambra State. The population consisted of 268 managers of 55 registered establishments that have business education graduates in their employment. One research question and one hypothesis tested at 0.05 level of significance were used. The instrument employed for data collection was fifteen item questionnaire. Descriptive statistics of mean and standard deviation were employed in analyzing data relative to the research question while t-test inferential statistics was employed in testing the hypothesis. The findings revealed that university business education graduates performed efficiently in 15 specified administrative functions and significant difference was not found in respondents’ mean ratings as a result of their establishments. It was concluded that the graduates studied performed efficiently in administrative functions articulated in the study. It was recommended that the planners and implementers of university business education programme should maintain their standards of nurturing their students to ensure continued efficient performance of the graduates in employment